The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fendo.2019.00368
|View full text |Cite
|
Sign up to set email alerts
|

Brown and Beige Adipose Tissue and Aging

Abstract: Across aging, adipose tissue (AT) changes its quantity and distribution: AT becomes dysfunctional with an increase in production of inflammatory peptides, a decline of those with anti-inflammatory activity and infiltration of macrophages. Adipose organ dysfunction may lead to age-related metabolic alterations. Aging is characterized by an increase in adiposity and a decline in brown adipose tissue (BAT) depots and activity, and UCP1 expression. There are many possible links to age-associated involution of BAT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 90 publications
1
117
0
2
Order By: Relevance
“…Titan mice also display higher levels of intra-abdominal fat, which correlates with hyperinsulinemia, whitening of BAT, and fat cells presence in the pancreas. BAT whitening is strongly linked to obesity (Kotzbeck et al, 2018) and becomes more prevalent during aging in both humans and rodents (Zoico et al, 2019). As mice age, small lipid droplets normally observed in brown adipocytes coalesce into a single vacuole (Brayton et al, 2012), as observed in Titan mice.…”
Section: Discussionmentioning
confidence: 99%
“…Titan mice also display higher levels of intra-abdominal fat, which correlates with hyperinsulinemia, whitening of BAT, and fat cells presence in the pancreas. BAT whitening is strongly linked to obesity (Kotzbeck et al, 2018) and becomes more prevalent during aging in both humans and rodents (Zoico et al, 2019). As mice age, small lipid droplets normally observed in brown adipocytes coalesce into a single vacuole (Brayton et al, 2012), as observed in Titan mice.…”
Section: Discussionmentioning
confidence: 99%
“…The UCP1-mediated proton leak is thereby specific to BAT thermogenesis: a diminished proton gradient permits an increased rate in the series of exothermic reactions generating the protein gradient, from the TCA cycle through the ETC, and increases the rate of collisions between protons and other molecules, generating substantial heat (24). Mitochondrial dysfunction and age-related hormonal changes that regulate UCP1 expression may also explain why BAT activation correlates negatively with age (25).…”
Section: Cellular Thermogenesismentioning
confidence: 99%
“…Since cold acclimation is able to recruit the BAT in obese patients, BAT activation may also improve obesity-associated insulin resistance and hyperglycemia [18]. The activity of adult brown and beige fat decreases with aging [19][20][21] and may contribute to the progression of chronic metabolic diseases. Taken together, these findings suggest that activating and recruiting brown and beige fat would be beneficial to improving overall metabolic health.…”
Section: Thermogenesis and Adipose Tissuementioning
confidence: 99%